Portrait of mental health literacy in schools: Knowledge exploration of counseling teachers - Pratiwi, Ratri; Rahmatulloh, Ainurizan Ridho; Rahimatussalisa, Rahimatussalisa; Nihayah, Maryama (Universitas Islam Negeri Raden Intan Lampung, 2022)
Mental health has an important implication for every teenager's life aspect, such as an ability to take action in education, friendship, family relation, and how they will go through their next life journey. School is an ideal place to help teenagers develop their mental health conditions, and the teacher is an essential factor as the service provider. This study aims to explore the mental health knowledge of counseling teachers to help students achieve a well-being condition. The research design and analysis techniques were a qualitative survey by distributing open questionnaires online to counseling teachers in junior and senior high school. The result of the research showed that the knowledge of participants about mental health in the school was less comprehensive. Most of the responses explained the emotional aspect (35%), whereas other aspects of knowledge (cognitive, habits, self-control, and social) are lower. Besides, knowledge about mental health in the school showed 26% of participant responses related to knowledge from the health aspect, whereas knowledge from being and loving aspect was lower. Another finding of this research was that most (57%) cases often handled by the participant are teenage naughtiness cases such as bullying, smoking, and stealing. Recommendations from this research are we need psychoeducation training and mental health for counseling teachers in the school.